Clare's Law, or the national Domestic Violence Disclosure Scheme: the contested legalities of criminality information sharing. (February 2015) - Grace, Jamie
Clare's Law has been a PR success for the police in England and Wales—the police have engaged directly with the media over the national roll-out of the Domestic Violence Disclosure Scheme. But the precise operation of the Scheme, at a doctrinal level, is unclear, and warrants further scrutiny (and, I would argue, reform) before a crisis of confidence in the Scheme is precipitated by a challenge by way of judicial review. Human rights case law concerning the procedural rights of (suspected) domestic violence perpetrators is the medium through which this piece explores the manner in which the Scheme currently operates on the basis of Home Office guidance and policy.